The Supraspinally Mediated Analgesic Effects of Zonisamide in Mice After Peripheral Nerve Injury Are Independent of the Descending Monoaminergic System - Mitsuo Tanabe; Yuichi Takeuchi; Hideki Ono (Elsevier, 2007)
We have previously demonstrated that the antiepileptic drug zonisamide supraspinally generates analgesic effects on thermal and mechanical hypersensitivity in mice after peripheral nerve injury. To further establish the neurochemical basis for the supraspinally mediated analgesic action of zonisamide, we measured spinal noradrenaline (NA), 3-methoxy-4-hydroxyphenyleneglycol (MHPG), serotonin (5-HT), 5-hydroxyindoleacetic acid (5-HIAA), and dopamine (DA) contents using HPLC with electrochemical detection in a murine neuropathic pain model that was prepared by partial ligation of the sciatic nerve (Seltzer model). Intraperitoneally or intracerebroventricularly administered zonisamide (50 mg/kg, i.p. and 30 µg, i.c.v., respectively), which almost completely reduced mechanical hypersensitivity, did not elicit any changes in spinal NA, MHPG, 5-HT, 5-HIAA, and DA contents. Moreover, the effectiveness of i.p. or i.c.v. administered zonisamide at reducing thermal and mechanical hypersensitivity was not influenced by intrathecally administered yohimbine (3 µg), an α2-adrenergic receptor antagonist. Thus, it appears that the supraspinally mediated analgesic effects of zonisamide are independent of the descending monoaminergic pain inhibitory system. Keywords:: zonisamide. neuropathic pain, descending noradrenergic system, monoamine, α2-adrenergic receptor